Effect of Hyperinsulinemia and Insulin Resistance on Endocrine, Metabolic, and Reproductive Outcomes in Non-PCOS Women Undergoing Assisted Reproduction: A Retrospective Cohort Study - Cai, Wang-Yu; Luo, Xi; Song, Jianyuan; Ji, Danpin; Zhu, Jun; Duan, Cuicui; Wu, Wei; Wu, Xiao-Ke; Xu, Jian (Frontiers in Medicine, 2022)
Objective: To evaluate the effect of hyperinsulinemia (HI) and insulin resistance (IR) on endocrine, metabolic and reproductive outcomes in women without polycystic ovary syndrome (PCOS) undergoing assisted reproduction. Materials and methods: The study included 1104 non-PCOS women undergoing in vitro fertilization/intracytoplasmic sperm injection-fresh embryo transfer. HI was evaluated by serum fasting insulin (FIN), and IR was evaluated by homeostatic model assessment of insulin resistance index (HOMA-IR). In addition, biometric, sex hormone and metabolic parameters were measured. Independent t-test, linear, and logistic regression examined associations between HI, IR and endocrine, metabolic, ovarian stimulation characteristics and reproductive outcomes. Results: Women with HI and IR had lower levels of progesterone, luteinizing hormone, follicle-stimulating hormone, estradiol, high-density lipoproteins, and increased levels of triglycerides low-density lipoproteins. For ovarian stimulation characteristics, those with HI and IR had a longer duration of stimulation, a higher total gonadotropin dose, and a lower peak estradiol level. Linear regression confirmed these associations. For reproductive outcomes, HI and IR were not associated with clinical pregnancy, live birth and miscarriage. Conclusions: HI and IR didn’t impair reproductive outcomes in non-PCOS women undergoing assisted reproduction.